2021
DOI: 10.33043/josep.1.1.55-66
|View full text |Cite
|
Sign up to set email alerts
|

Special and Inclusive Education in Southern Africa

Abstract: Children with special education needs possess unique learning characteristics which may inhibit their effective learning in mainstream, general education classes. Special education practices are therefore designed to address the educational needs of students with disabilities through various strategies including thorough assessments of students’ characteristics, individualized curriculum planning, and provision of essential services and resources to maximize learning. Although there is extensive research on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…In line with literature (Chitiyo and Dzenga, 2021; Haitembu, 2014; Mokaleng and Möwes, 2020), this study revealed that lack of understanding of what inclusion entails is hindering the IE policy's responsiveness to gender non‐conforming learners.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In line with literature (Chitiyo and Dzenga, 2021; Haitembu, 2014; Mokaleng and Möwes, 2020), this study revealed that lack of understanding of what inclusion entails is hindering the IE policy's responsiveness to gender non‐conforming learners.…”
Section: Resultssupporting
confidence: 86%
“…The findings of this study further concur with literature ( i.e ., Chitiyo and Dzenga, 2021; Haitembu, 2014; Joubert, Van Wyk, and Rothmann, 2011; Mokaleng and Möwes, 2020; UNESCO, 2016) that lack of training for teachers and lack of information are some of the factors that are preventing fully inclusion in schools. The success of any educational policy and programme depends on its implementation at schools by the teachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, instead of epistemological access, the goal of special and inclusive education is reduced to a therapeutic arena for remedying disabilities. Such stipulations may affect how regular teachers implement inclusivity in mainstream education (Chitiyo & Dzenga, 2021).…”
Section: Inclusive Education: Policy Practice and Researchmentioning
confidence: 99%